ECONOMIC EVALUATION OF COMBINED THERAPY OF ARTERIAL HYPERTENSION BY MARKOV’S MODELING - N. S. Maksimchuk-Kolobova; E. I. Tarlovskaya; S. V. Malchikova (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate the economic effectiveness of the combined two-drug antihypertensive therapy in patients with arterial hypertension (HT) and high cardiovascular risk by Markov’s modeling.Material and methods. Patients (n= 65; 19 males and 46 females) with essential HT accompanied by metabolic disorders, history of previous ineffective antihypertensive therapy were included into the study. Patients were randomized into 2 groups. Group V/A was treated with valsartan and amlodipine in fixed-dose combinations of 160/5 and 160/10 mg depending on blood pressure (BP) level. Patients of group L/A were treated with losartan 100 mg and amlodipine 5 or 10 mg daily. Treatment duration was 24 weeks. Changes in BP level, and left ventricular hypertrophy (LVH) regression were assessed. Economic evaluation was performed on the basis of modeling with specialized software Decision Tree 4.xla.Results. Effect of the two variants of combination therapy on LVH was used to estimate treatment effectiveness and to build the model. Patients were distributed according to the left ventricular mass (LVM) at baseline and after 24 weeks of therapy. Significant decrease in LVM was observed in V/A group: from 225.1±71.7 to 186.3±44.5 g (p<0.05). There was no LVM dynamics in L/A group. The model took into account economic and frequency factors for 10 years forecast. V/A therapy is able to prevent 94 deaths, 22 strokes, and 64 myocardial infarction per 1000 patients. Absence of need in treatment of these prevented events can save about 5.5 million RUR for every 1000 patients. It would reduce the total costs per patient during 10 years. V/A therapy is able to save maximal number of quality adjusted life years (QALY) due to LVM regression (5.016 years). L/A combination is the most economical variant of pharmacotherapy due to low cost of treatment (16.491.25 RUR per 1 QALY). It would take 286.698.7 RUR additionally for one additional QALY in the treatment with V/A, and it is economically effective.Conclusion. Treatment with V/A fixed-dose combinations shows higher antihypertensive and cardioprotective efficacy in comparison with that in L/A combination therapy. It reduces a risk of acute myocardial infarction, stroke and death more effectively. V/A therapy gains the maximal number of life years and QALY due to LVM regression.L/A combination is the most cost-effective in terms of cost of life year gained and QALY. L/A combination allows to save costs due to lower cost of treatment.